Development of a serious game for Portuguese Sign Language - Soares, Filomena (2016)
Human-computer interaction by gesture recognition has been a technology increasingly powerful and with a wide range of applications. The aim of this research is to take advantage of these resources and tools, developing an application for gesture recognition in Portuguese Sign Language (PSL) focused in helping disabled deaf and/or mute and hearing children to learn PSL. The PSL involves the use of hands and facial expressions to interact, where the output of the communication (talk) comes from the hands and/or body and the input comes from the eyes observation (hear). This paper presents a serious game for children in the 1st cycle (primary Portuguese school) between the ages of 6 to 10 years. The game is based on a story, in order to promote the motivation of the students in the learning of the Portuguese Sign Language.